Integrated conceptual framework for managerial decision-making and project management: structural, behavioral, and value-based aspects - Abasova, A.; Abdulrahmanova, Z.; Askerova, I.; Абасова, А. А.; Абдулрахманова, З. А.; Аскерова, І. А. (Харківський національний автомобільно-дорожній університет, 2026)
This study develops an integrated conceptual framework for managerial decision-making that combines structural, behavioral, and informational dimensions with project management and value-based organizational considerations. The framework systematically links six key decision-making determinants, such as managerial value judgments, decision environment, information constraints, behavioral limitations, negative consequences, and interdependence of decisions, to five main decision-making mechanisms, including hierarchical management, regulatory rules, bilateral interaction, group-based, and matrix approaches. By embedding these elements within a cyclical, iterative process of problem identification, alternative development, decision evaluation, implementation, and feedback with contingency planning, the study emphasizes the dynamic and adaptive nature of managerial decisions. The proposed model also integrates project management perspectives, illustrating how decision-making determinants and mechanisms align with project lifecycle stages and organizational objectives. The meaning-based value level highlights the influence of organizational culture, stakeholder expectations, and systemic factors on decision priorities and interpretations of success. By mapping these interactions, the framework provides a multidimensional tool for analyzing decision performance, optimizing project outcomes, and enhancing organizational adaptability in complex and uncertain environments. This approach differs from traditional models by emphasizing the interconnectedness of structural, behavioral, informational, and value-driven considerations within managerial decision-making. It supports evidence-based practices, fosters alignment between operational efficiency and strategic goals, and strengthens the resilience, coordination, and resource efficiency of organizations. The framework can be applied across diverse organizational types and sectors, providing both theoretical insights and practical guidance for managers seeking to enhance decision effectiveness in contemporary project-oriented environments.
Інтегрована концептуальна модель управлінського прийняття рішень та проєктного менеджменту: структурні, поведінкові і ціннісні аспекти
Keywords: managerial decision-making; decision determinants; decision mechanisms; project management; organizational culture; stakeholder expectations; adaptive management; strategic alignment; управлінське прийняття рішень; детермінанти рішень; механізми прийняття рішень; проєктний менеджмент; організаційна культура; очікування стейкхолдерів; адаптивне управління; стратегічне узгодження; 338.2422:005.51:005.8; 10.30977/ЕТК.2225-2304.2026.47.194